1997
DOI: 10.1021/ma9615112
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric Study of Thermal Cooperative Transitions in Poly(N-vinylcaprolactam) Hydrogels

Abstract: Structural cooperative transitions in thermosensitive nonionic hydrogels of poly(N-vinylcaprolactam) (PVCa) were studied using high-sensitivity differential scanning calorimetry (HS-DSC). The thermoshrinking of the PVCa gel is endothermic, much like first-order phase transitions. According to the HS-DSC data, the gel system undergoes two successive cooperative transitions between 25 and 50 °C. The low-temperature transition (31.5 °C) is proposed to be associated with the microsegregation resulting in formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 47 publications
3
107
0
Order By: Relevance
“…A gel sample was kept in a 9.4 N 10 -3 M (1.2 critical micelle concentration (CMC) 20) ) solution of SDS at 20 8C for 8 d until equilibrium was reached, then at 20 8C in 43.2 N 10 -3 M (5.3 CMC) solution of SDS for 4 d and at 60 8C in 43.2 N 10 -3 M solution of SDS for 2 h. X-ray scattering experiments were performed as it was specified earlier 21) . Fine suspensions of the complex gel, swollen in 43.2 N 10 -3 M solution of SDS, were prepared in the same surfactant solution using a hand-operated glass homogenizer of biological tissues 9) . Typically, the average size of gel particles of the suspension was about 10 lm and the polymer concentration in the suspension was about 1 mg/ml.…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…A gel sample was kept in a 9.4 N 10 -3 M (1.2 critical micelle concentration (CMC) 20) ) solution of SDS at 20 8C for 8 d until equilibrium was reached, then at 20 8C in 43.2 N 10 -3 M (5.3 CMC) solution of SDS for 4 d and at 60 8C in 43.2 N 10 -3 M solution of SDS for 2 h. X-ray scattering experiments were performed as it was specified earlier 21) . Fine suspensions of the complex gel, swollen in 43.2 N 10 -3 M solution of SDS, were prepared in the same surfactant solution using a hand-operated glass homogenizer of biological tissues 9) . Typically, the average size of gel particles of the suspension was about 10 lm and the polymer concentration in the suspension was about 1 mg/ml.…”
Section: Experimental Partmentioning
confidence: 99%
“…In the course of the cloud point determination, the suspension was heated with an average rate of about 1 degree per min. Calorimetric measurements were performed with a differential adiabatic scanning microcalorimeter DASM-4 ("BIOPRIBOR", Pushchino, Russia) at a heating rate of 1 degree/min using the procedure described in detail elsewhere 9) . The apparent heat capacity of the PDADMA-Cl/SDS complex network was calculated per residue of the stoichiometric PDADMA-Cl/SDS complex (M = 391.6 Da).…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to their temperature-sensitive counterparts poly(N-vinylcaprolactam) (PNVC) is favored but less investigated. [16][17][18] PNVC has many important properties, e.g. solubility in water and in other solvents, [18,19] high stability to hydrolysis, [20] and LCST varying between 32 and 33°C similar to NIPAAm and also less cytotoxic than (NIPAAm).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was shown that in aqueous solutions, PVCa gels can absorb both ionic molecules as a result of polar interactions and nonionic organic compounds as a result of hydrophobic interactions between the hydrophobic groups of PVCa and the hydrophobic groups of organic molecules. 3,4 It is well known that dyes are widely used in analytical chemistry for the photometric-selective quantitative determination of metal ions in aqueous solutions. The methods of determination are based on the property of the dyes to form chelate complexes with ions of certain metals.…”
Section: Introductionmentioning
confidence: 99%